Prevalence and distribution of resistant genes of antibiotics, heavy metals and biocides in some enterobacteria species - Khalaf, Samir M; Essa, Muhsin A (Vojenské zdravotnické listy, 2024)
The problem of bacterial resistance to antibiotics has become a global issue and a major health challenge that requires continuous studies on how this resistance develops and spreads, and its relationship to resistance to other factors such as heavy metals and biocides. The current study aimed to determine the prevalence and distribution of antibiotics, heavy metals, and biocides-resistant genes on the chromosomes and plasmids of some Enterobacteria species. The results showed that antibiotics resistant genes (blaCTX, sul 1) were present in all isolates except for Klebsiella pneumoniae chromosome, while for heavy metals resistant genes, czcA detected in all isolates except for K. pneumoniae plasmid, ncc gene was only detected in the chromosome of Escherichia coli O157.H7 and E. coli, and plasmid of E. coli O157.H7. biocides gene (qacE∆1) was present in all isolates except for the E. faecalis chromosome. The current study resulted that the studied resistance genes spread clearly among the types of Enterobacteria, and this reflects the possibility of transmission of these genes among the bacteria present in this habitat.
Keywords: Enterobacteriaceae; polymerázová řetězová reakce; dezinficiencia; antibiotická rezistence; Disinfectants; Polymerase Chain Reaction; Drug Resistance; plazmidy; Metals, Heavy; Genetic Techniques; genetické techniky; Plasmids; Drug Resistance, Microbial; léková rezistence; těžké kovy